Recent trends in algebraic development techniques : 21st International Workshop, WADT 2012, Salamanca, Spain, June 7-10, 2012, Revised Selected Papers - Palomino, Miguel; Marti-Oliet, Narciso (Lecture notes in computer science, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 21st International Workshop on Algebraic Development Techniques, WADT 2012, held in June 2012, in Salamanca, Spain. The 16 revised papers presented were carefully reviewed and selected from 25 presentations. The workshop deals with the following topics: foundations of algebraic specification; other approaches to formal specification including process calculi and models of concurrent, distributed and mobile computing; specification languages, methods, and environments; semantics of conceptual modeling methods and techniques; model-driven development; graph transformations, term rewriting and proof systems; integration of formal specification techniques; formal testing and quality assurance; validation, and verification.